MENINGKATKN HASIL BELAJAR IPS SUB TEMA KEBERAGAMAN BUDAYA BANGSAKU MELALUI MODEL STUDENT TEAM ACHIVEMENT DEVISION (STAD) DENGAN MEDIA GAMBAR KELAS IV SD - Damayanti, Damayanti (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to improve students' learning outcomes in social science subjects Sub Theme of Cultural Diversity of Bangsaku Through Learning Model Student Team Achivemenet Devision With Picture Media Grade IV SD Negeri 4 Ambeua Kaledupa District. The design and model used in this study kemmis and Taggart model which includes planning, implementation, observation, reflection and re-planning and the type of research conducted by researchers is a type of class action research (PTK). From the evaluation of cycle I obtained data from 22 students, there were 13 students who obtained a KKM score of 65 or classically reached 59% and 9 students who did not complete 41% with an average score of 65.52 and a score weight of 1,443. while in cycle II classically student learning outcomes increased whereas out of 22 students, there were 20 students who obtained a KKM score of 65 or classically reached 91% and 2 students who did not meet the KKM 9% with an average score of 85.22 and a score weight achieved as much as 1,875. Based on the results of the study, it was concluded that the application of student team achievement team learning model can improve students' learning outcomes in social science subjects in grade IV of SD Negeri 4 Ambeua Kaledupa Regency.